The relationship between blood lipid and risk of psoriasis: univariable and multivariable Mendelian randomization analysis - Zhang, Zeng-Yun-Ou; Jian, Zhong-Yu; Tang, Yin; Li, Wei (Frontiers in Immunology, 2023)
Background Psoriasis is a chronic inflammatory skin disease. Dyslipidemia may be a risk factor of psoriasis. But the causal relationship between psoriasis and blood lipid still remains uncertain. Methods The two data of blood lipid were obtained from UK Biobank (UKBB) and Global Lipid Genetics Consortium Results (GLGC). The primary and secondary database were from large publicly available genome-wide association study (GWAS) with more than 400,000 and 170,000 subjects of European ancestry, respectively. The psoriasis from Finnish biobanks of FinnGen research project for psoriasis, consisting of 6,995 cases and 299,128 controls. The single-variable Mendelian randomization (SVMR) and multivariable Mendelian randomization (MVMR) were used to assess the total and direct effects of blood lipid on psoriasis risk. Results SVMR estimates in primary data of blood lipid showed low-density lipoprotein cholesterol (LDL-C) (odds ratio (OR): 1.11, 95%, confidence interval (CI): 0.99−1.25, p = 0.082 in stage 1; OR: 1.15, 95% CI: 1.05−1.26, p = 0.002 in stage 2; OR: 1.15, 95% CI: 1.04−1.26, p = 0.006 in stage 3) and triglycerides (TG) (OR: 1.22, 95% CI: 1.10−1.35, p = 1.17E-04 in stage 1; OR: 1.15, 95% CI: 1.06−1.24, p = 0.001 in stage 2; OR: 1.14, 95% CI: 1.05−1.24, p = 0.002 in stage 3) had a highly robust causal relationship on the risk of psoriasis. However, there were no robust causal associations between HDL-C and psoriasis. The SVMR results in secondary data of blood lipid were consistent with the primary data. Reverse MR analysis showed a causal association between psoriasis and LDL-C (beta: -0.009, 95% CI: -0.016− -0.002, p = 0.009) and HDL-C (beta: -0.011, 95% CI: -0.021− -0.002, p = 0.016). The reverse causation analyses results between psoriasis and TG did not reach significance. In MVMR of primary data of blood lipid, the LDL-C (OR: 1.05, 95% CI: 0.99–1.25, p = 0.396 in stage 1; OR: 1.07, 95% CI: 1.01–1.14, p = 0.017 in stage 2; OR: 1.08, 95% CI: 1.02–1.15, p = 0.012 in stage 3) and TG (OR: 1.11, 95% CI: 1.01–1.22, p = 0.036 in stage 1; OR: 1.09, 95% CI: 1.03–1.15, p = 0.002 in stage 2; OR: 1.07, 95% CI: 1.01–1.13 p = 0.015 in stage 3) positively correlated with psoriasis, and there had no correlation between HDL-C and psoriasis. The results of the secondary analysis were consistent with the results of primary analysis. Conclusions Mendelian randomization (MR) findings provide genetic evidence for causal link between psoriasis and blood lipid. It may be meaningful to monitor and control blood lipid level for a management of psoriasis patients in clinic.